Pemanfaatan Arang Aktif Berbahan Pelepah Kelapa Sawit sebagai Adsorben Pemurnian Biodiesel dari Minyak Curah - Jeremia Yosafat Rios; Mohammad Prasanto Bimantio; Adi Ruswanto (Program Studi Teknologi Hasil Pertanian, 2024)
The trans esterified biodiesel cannot be used immediately, because it still contains reaction residue and impurities. So it needs purification. One of them can use activated charcoal. The material used to make activated charcoal is palm fronds. Palm fronds contain lignocellulosic components, namely 25.08% cellulose, 24.06% hemicellulose and 18.46% lignin. This component can be applied as an adsorbent. The aim of the research was to determine the size of the activated charcoal and the length of time the adsorption of activated charcoal had an effect on biodiesel purification and to find out the best formulation from the ratio of the size of activated charcoal and the adsorption time to biodiesel purification. This study used a complete block design (RBL), with two factors, namely the ratio of activated charcoal size (A) and adsorption time (B) carried out 2 repetitions. For the average results of the analysis of this study, the acid number was 7.66 mg-KOH/gr, the saponification number was 251.75 mg KOH/gr, the density was 0.93 g/ml, the viscosity was 31.64 cst, the chromameter colour was 3.43, the impurities content was 4 .4% and GC-MS contained the most compounds, namely 9-Octadecenoic acid (Z)-, methyl ester with a surface area of 42.80% and a retention time of 27.292 minutes. The conclusion of the study is that the size comparison of activated charcoal and adsorption time made from palm fronds can adsorb impurities in biodiesel.